A method for designing strategy maps using DEMATEL and linear programming. Issue 8 (18th September 2017) - López-Ospina, Héctor; Quezada, Luis E.; Barros-Castro, Ricardo A.; Gonzalez, Miguel A.; Palominos, Pedro I.
Abstract : Purpose: The purpose of this paper is to propose a quantitative methodology for the identification of the causal relationships between strategic objectives in a strategy map of a balanced scorecard. This is done to face the possible weaknesses described in the literature regarding the causal links and the difficulty in validating the relationships. Design/methodology/approach: The proposed method combines the multi-criteria decision-making method called decision-making trial and evaluation laboratory (DEMATEL) and an optimization model. DEMATEL is used to establish the importance of the strategic relations between strategic objectives, and the optimization model is used to find the relations that are more "important" and should be included in the strategy map. The method was created by reviewing the existing literature, modeling the problem, and applying it in a company. Findings: The most important results of applying this methodological design include that the proposed method maintains the BSC classical structure; it also enables the generation of several alternatives to support the decision-making process in terms of strategic objectives for a better organizational performance. Practical implications: The method facilitates the decision-making process by presenting several alternatives of strategy maps according to different levels of organizational criteria. In fact, these alternatives help the organization in focusing on the most important aspects of the strategy map. Consequently, managers may identify where to pay more attention and resources in order to achieve the most important objectives of the company. Hence, this method, as a support for decision makers, enables (and requires) the active participation of senior managers and any kind of decision makers in creating and valuating objectives, relations, constraints, importance, and parameters of the optimization model. Originality/value: DEMATEL has been used to design strategy maps. The contribution of the paper is the use of a linear programming model to select those relationships that should be included in the strategy map. It allows manager to focus on those strategic elements that are important from a strategic point of view. The application in a company showed that the contribution is not only theoretical but practical as well.